1995
DOI: 10.1103/physrevc.52.740
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the new isotopeBa114and search for its α and cluster radioactivity

Abstract: Using the on-line mass separator at the Gesellschaft fur Schwerionenforschung Unilac we produced Ba through the Ni( Ni, 2n) Ba reaction and measured its production cross section to be 0.20+o 09 pb. The new isotope Ba represents the heaviest N = Z+ 2 nucleus known to date. With KE-E telescopes we measured the total (P-decay) half-life to be Tp = 0.43+o~s s and the partial o.-decay half-life to be T ) 1.2 x 10 s (1 Mev( E' ( 4 MeV) for Ba. With track detectors we found a half-life for spontaneous C emission T& … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 12 publications
(10 reference statements)
4
53
0
1
Order By: Relevance
“…The BaF + ions were caught on a stopper foil at the centre of an array of ∆E-E silicon-plus-plastic-scintillator telescopes. In the initial experiment [9,10], the observation of three 12 C decay events was reported, but following the second experiment [16,17] with improved background subtraction, these claims were retracted. In that work, the half-life of 114 Ba was reported to be 0.43…”
Section: +013mentioning
confidence: 99%
See 2 more Smart Citations
“…The BaF + ions were caught on a stopper foil at the centre of an array of ∆E-E silicon-plus-plastic-scintillator telescopes. In the initial experiment [9,10], the observation of three 12 C decay events was reported, but following the second experiment [16,17] with improved background subtraction, these claims were retracted. In that work, the half-life of 114 Ba was reported to be 0.43…”
Section: +013mentioning
confidence: 99%
“…Another interesting aspect in this region is the prediction of cluster radioactivity [7]. It has been widely reported that the most promising candidate for this type of decay in the region is the 12 C decay 114 Ba→ 102 Sn [8][9][10], and that the theoretical predictions of the partial half-life depend very sensitively on the Q value for 12 C emission (Q12 C ) [8]. The value of Q12 C is therefore an important quantity in the design of experiments to search for this novel decay mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They range from 221 Fr up to 242 Cm. The emission of 14 C, 20 O, 23 F, [24][25][26] Ne, [28][29][30] Mg, and 32,34 Si has been observed. The common factor of all cluster radioactivity events is the heavy-mass residue which is in the neighborhood of the doubly-magic 208 Pb.…”
Section: Introductionmentioning
confidence: 99%
“…In 1995 Guglielmetti et al announced in Identification of the new isotope 114 Ba and search for its α and cluster radioactivity the discovery of 114 Ba [15]. 114 Ba was produced at the Gesellschaft für Schwerionenforschung Unilac via the fusion evaporation reaction 58 Ni( 58 Ni,2n) 114 Ba at 4.2 MeV/u and identified using an on-line mass separator.…”
Section: Bamentioning
confidence: 99%